A New Record of Distribution of Scaphidium quadrimaculatum Oliver (Scaphidiidae : Coleoptera) from Indian Region with Redescription - Chandra, Avinash; Shivaramakrishnan, V. R. (Indian Forester, 1986)
Scaphidium quadrimaculiatum Oliver (Family Scaphidiidae: Coleopiera) has been recorded from India for the first time. Earlier records and figures are inadequate and confusing, hence the need for detailed description.